2005
DOI: 10.1128/ec.4.1.90-94.2005
|View full text |Cite
|
Sign up to set email alerts
|

The G 1 Cyclin Cln3 Regulates Morphogenesis in Candida albicans

Abstract: In Saccharomyces cerevisiae, the G 1 cyclin Cln3 initiates the Start of a mitotic cell cycle in response to size and nutrient inputs. Loss of Cln3 delays but does not prevent Start, due to the eventual Cln3-independent transcription of CLN1 and CLN2. When unbudded cells of the human pathogen Candida albicans were depleted of the G 1 cyclin Cln3 they increased in size but did not bud. Thus, unlike S. cerevisiae, Cln3 is essential for budding in C. albicans. However, eventually the large unbudded cells spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 20 publications
3
78
0
2
Order By: Relevance
“…For example, C. albicans yeast cells treated with either the DNAreplication inhibitor hydroxyurea (HU) or the microtubule toxin nocodazole exhibited significant cell elongation (Bai et al, 2002;. Similar growth also occurs as the result of switching off the expression of either the G 1 cyclin Cln3p Chapa y Lazo et al, 2005) or one of the mitotic cyclins Clb2p and Clb4p (Bensen et al, 2005). Furthermore, deletion of CDC4, which encodes a component of the ubiquitin ligase SCF Cdc4p and is thought This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E06 -05-0442) on December 20, 2006. to have a role in determining cellular events around the G 1 /S transition, or depleting the polo-like kinase Cdc5p, which is required for mitotic exit, causes constitutive filamentous growth (Bachewich et al, 2003;Atir-Lande et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, C. albicans yeast cells treated with either the DNAreplication inhibitor hydroxyurea (HU) or the microtubule toxin nocodazole exhibited significant cell elongation (Bai et al, 2002;. Similar growth also occurs as the result of switching off the expression of either the G 1 cyclin Cln3p Chapa y Lazo et al, 2005) or one of the mitotic cyclins Clb2p and Clb4p (Bensen et al, 2005). Furthermore, deletion of CDC4, which encodes a component of the ubiquitin ligase SCF Cdc4p and is thought This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E06 -05-0442) on December 20, 2006. to have a role in determining cellular events around the G 1 /S transition, or depleting the polo-like kinase Cdc5p, which is required for mitotic exit, causes constitutive filamentous growth (Bachewich et al, 2003;Atir-Lande et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…These conditions more-or-less mimic certain host conditions. Interestingly, recent experiments have revealed a seemingly new mechanism for induction of filamentous growth that is caused by the perturbation of cell-cycle progression and is, in at least some cases, independent of the cAMP/PKA and MAP-kinase pathways (Bai et al, 2002;Bachewich et al, 2003;Andaluz et al, 2006;AtirLande et al, 2005;Bensen et al, 2005;Chapa y Lazo et al, 2005). An intriguing observation is that interfering with either an early or a late cell-cycle event, or with events thought to activate distinct cell-cycle checkpoints, appears to have strikingly similar effects on cell morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Ccn1p/Cln1p does not play a major role in morphogenesis (Loeb et al, 1999), whereas Hgc1p regulates hyphal growth under all hypha-inducing conditions (Zheng and Wang, 2004). Intriguingly, it has been shown that Cln3p-depleted cells spontaneously form hyphae under yeast growth conditions, suggesting that its activity negatively regulates the yeast-hyphal transition (Bachewich and Whiteway, 2005;Chapa y Lazo et al, 2005). Deletion of the forkhead transcription factor Fkh2p is associated with increased levels of the B-type cyclin CaClb4p and constitutive pseudohyphal growth (Bensen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cells lacking either of the cyclins Cln3p or Ccn1p and induced to form hyphae also show the phenotype where germs tubes initially form normally but subsequently become swollen at the tip (Loeb et al, 1999b;Chapa y Lazo et al, 2005;Bachewich and Whiteway, 2005).…”
Section: Control Of Vesicle Trafficmentioning
confidence: 99%
“…HGC1 is only expressed in hyphae and is required for hyphal growth. Yeast growth in C. albicans requires the CLN3 homologue (Chapa y Lazo et al, 2005;Bachewich and Whiteway, 2005). CLN3 is essential for viability, but cells can be depleted of Cln3p using expression from the highly regulatable MET3 promoter.…”
Section: Cdk1mentioning
confidence: 99%